Current Status of the Radiologic Assessment of Diverticular Disease - Kandagatla, Pridvi G.; Stefanou, Amalia J. (Clinics in Colon and Rectal Surgery, 2018)
Radiologic assessment plays a vital role in the management of diverticulitis. It not only helps in the diagnosis, but also helps to guide the management. As technology has progressed, different modalities have offered insight into the treatment of this disease process. Through various trials and studies, certain modalities stand above the rest in terms of sensitivity and specificity. Computed tomography (CT) imaging has also proved to help us guide the management through a grading system. Newer studies show us the advantages of other modalities such as ultrasound and magnetic resonance imaging (MRI). Though there is much research yet to be done with these modalities, they do show a lot of potential.
Keywords: computed tomography; acute diverticulitis; imaging; management